(untitled) (MAUSAM, 2021)
This research paper represents the search of faults/ fractures/ shear zones/ altered zones, to find out mineral target zones in part of Shivpuri district, M.P. Geologically, the study area is represented by Vindhyan Supergroup of Meso to Neoproterozoic age. The area is mainly covered by alluvium which is characterized river gravels, sand and residual soil. The gravity survey was carried out with a station density of 1 gravity station per 2.5 sq km along with elevations of each gravity stations covered 2800 sq km. The rock samples have been collected from different litho-units of the study area for measurement of physical property (Density) which are useful for understanding & evaluating of geological response. The general trend of contour pattern of Bouguer gravity is NW-SE directions. Bouguer gravity anomaly contour map is characterized by broad gravity ‘high’ in southern part whereas ‘low’ in northern part which inferred depression of basement toward the north. The nosing in aligned approximately NW-SE direction is recorded in central part which may be interpreted as inferred lineament and it is clearly reflected on residual gravity map. The regional gravity anomaly aligned in NW-SE is characterized by broad gravity ‘high’ in southern part whereas ‘low’ in northern part which reflects basement deepening towards north. The majority of Euler 3D solutions are falling on linear bodies (inferred lineament) with varying depths from 0.5 to 2.5 km.